Bacteriological profile and antibiotic sensitivity patterns of burn wound in delayed presenting cases of burn at a tertiary care centre in India - Khurram, Mohammed Fahud; Maurya, Sudheer Kumar; Maurya, Rajesh Kumar; Yaseen, Mohammad (International Journal Of Community Medicine And Public Health, 2018)
Background: In developing world, there is a wide gap between the number of burn patients and resources of management. Patients reports to tertiary centre late. So in our study, we have assessed the late presenting cases of burns, their epidemiological data, bacteriological profile and antibiotic sensitivity patterns of burn wounds. Methods: This is a prospective study conducted in Jawaharlal Nehru Medical College and associated hospital, Aligarh Muslim University, Aligarh from December 2015 to November 2017,where all the delayed presenting (>5 days) cases of burn involving 20% to 60% body surface area having no other comorbidity and age ranging from 5 years to 60 years were included and evaluated. Results: In our study, total 104 patients were included. Total 281 swabs were found to be culture positive, out of which 243 were monobacterial dominant. The Pseudomonas aeruginosa was found in 29.22% cases, E.coli in 23% cases, Klebsiella pneumoniae in 20.16%, Citrobacter in 9.88% cases, MRSA in 04.53%, MSSA in 5.35% cases. P.aeruginosa was mainly sensitive to piperacillin + tazobactum in 74.64%. Escherichia colli was sensitive to piperacillin + tazobactum in 75% cases, to collistin in 73.21% cases. Conclusions: Burn injuries are very common specially in developing countries where dependence over the traditional way of cooking is more. Use of antibiotic as per bacterial culture and sensitivity report, early surgical intervention and proper burn wound care at tertiary care centre reduce the morbidity and mortality of burn patients.